UNIFIED TEMPLATE OF GEOREFFERENCED IMAGES FOR VISUAL CORRELATIONEXTREME NAVIGATION SYSTEM - Mukhina, Maryna (Proceedings of National Aviation University (archive), 2016)
The article considers existing methods of image feature detection. Descriptive representation of unified template is proposed based on Speed-Up Robust Feature (SURF) method. The requirements and structure of database of unified template are developed including the reliability factor of each image feature. Experiments evidences the decreasing of memory volume for database and of computational time of recognition.